PENGARUH VARIASI JARAK PELAT HELICAL TERHADAP KAPASITAS DAYA DUKUNG TEKAN PONDASI HELICAL PILE PADA TANAH GAMBUT DENGAN METODE CONSTANT STRESS OF PENETRATION - Fadhilah, Randy; Fatnanta, Ferry; Nugroho, Soewignjo Agus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A study of the determination of helical pile bearing capacity based on static load test on peat soil has been done previously. However, the research is still covered in one method of loading which is the Constant Rate of Penetration (CRP). Therefore, it is deemed necessary to apply static load test on the helical pile on peat soils by using other loading method as a comparison. One of the test methods is Constant Stress of Penetration loading test. In this research, the helical piles used amounted to 9 piles. The loading were performed in six stages with a total load of 1200 kg. The data obtained from this test consist of settlement curve against time and loading curve against settlement. Determination of bearing capacities of helical piles were based on individual bearing and cylindrical shear method, and interpretation of test data based on Tangent Intersection and Terzaghi & Peck method. The results of the interpretation of the test data indicate that in the LMS (Large-Medium-Small)and LM (Large-Medium)helical pile groups have effective space between helical plates is from 20 to 30 cm. While in the LL (Large-Large) helical pile group, the effective space between the helical plates is from 30 to 50 cm. Based on comparison of calculation result with interpretation of test data, peat coefficient value used is 8%. Interpretation of test data tends to be closer to the cylindrical shear method with a standard error of 0.74 than the individual bearing method with standard error of 1.03.Keywords: Helical Pile, Peat Soil, Individual Bearing, Cylindrical Shear